Neuroinflammation as modifier of genetically caused neurological disorders of the central nervous system: Understanding pathogenesis and chances for treatment. Issue 9 (1st June 2017) - Groh, Janos; Martini, Rudolf
Abstract: Genetically caused neurological disorders of the central nervous system (CNS) are usually orphan diseases with poor or even fatal clinical outcome and few or no treatments that will improve longevity or at least quality of life. Neuroinflammation is common to many of these disorders, despite the fact that a plethora of distinct mutations and molecular changes underlie the disorders. In this article, data from corresponding animal models are analyzed to define the roles of innate and adaptive inflammation as modifiers and amplifiers of disease. We describe both common and distinct patterns of neuroinflammation in genetically mediated CNS disorders and discuss the contrasting mechanisms that lead to adverse versus neuroprotective effects. Moreover, we identify the juxtaparanode as a neuroanatomical compartment commonly associated with inflammatory cells and ongoing axonopathic changes, in models of diverse diseases. The identification of key immunological effector pathways that amplify neuropathic features should lead to realistic possibilities for translatable therapeutic interventions using existing immunomodulators. Moreover, evidence emerges that neuroinflammation is not only able to modify primary neural damage‐related symptoms but also may lead to unexpected clinical outcomes such as neuropsychiatric syndromes. Main Points: A commonality of distinct genetic CNS disorders is neuroinflammation. Here, the role of inflammation as a modifier and amplifier of disease including inflammation‐related target structures are analyzed. Moreover, translational options are discussed.